Identifying The Determinants Of Tourist's Environmentally Responsible Behavior: Extending The Cab Model With Generativity In Bromo Tengger Semeru National Park - Novita Uki Hutami; Yulita Suryantari; Imam Nur Hakim; Feti Fatimatuzzahroh (Jurnal Kepariwisataan Indonesia: Jurnal Penelitian dan Pengembangan Kepariwisataan Indonesia, 2026)
Tourism development in rural mountain protected areas can bring economic benefits to local communities while increasing environmental pressure on fragile ecosystems. In Bromo Tengger Semeru National Park (BTSNP), rising visitor numbers have caused environmental problems such as littering, wildfires, and vegetation disturbance. This study aims to examine how ecotourism perception, satisfaction, and generativity influence environmentally responsible behavior (ERB) among visitors in mountain conservation areas facing increasing ecological pressure. Grounded in an extended Cognitive-Affective-Behavior (CAB) framework, this study integrates generativity as a psychosocial driver of ERB. Data were collected from 287 tourists through structured questionnaires and analyzed using SEM and multi-group analysis (MGA) to examine structural relationships and intergenerational differences. The results show that generativity significantly influences ERB, emerging as the strongest predictor in the model. Ecotourism perception (EP) significantly increases tourist satisfaction but does not directly influence ERB. Satisfaction neither directly affects ERB nor mediates the relationship between EP and ERB. MGA further indicates that the relationship between generativity and ERB was significant only among Gen Y tourists, although this difference should be interpreted cautiously. These findings challenge the linear assumption of the CAB framework by showing that generativity, as a future-oriented factor, plays a more important role than cognitive and affective evaluation in shaping ERB. They also offer practical implications for promoting long-term socio-ecological management through targeted visitor engagement and strengthened governance strategies in protected mountain areas.